Determination of parameters for digital meter of doppler radars systems for the artillery systems - Kaninskiy, Valeriy; Budaretskiy, Yuriy; Grabchak, Volodymyr; Prokopenko, Vyacheslav (Видавництво Львівської політехніки, 2010)
Analytical choice of the digital meter parameters based on digital systems of phase synchronization (DSPS) is considered, also the simulation model design in order to perform the optimization of its parameters and to determine the temporary characteristics and the accuracy of the motion parameters of objects estimating, for the systems with autonomous navigation and ballistic training artillery systems.
Keywords: digital system of phase synchronization; analytical and simulation models